2004
DOI: 10.1124/jpet.104.075184
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Cocaine Administration Increases Membrane Excitability of Pyramidal Neurons in the Rat Medial Prefrontal Cortex

Abstract: Although the medial prefrontal cortex (mPFC) plays a critical role in cocaine addiction, the effects of chronic cocaine on mPFC neurons remain poorly understood. Here, we performed visualized current-clamp recordings to determine the effects of repeated cocaine administration on the membrane excitability of mPFC pyramidal neurons in rat brain slices. Following repeated cocaine administration (15 mg/kg/day i.p. for 5 days) with a 3-day withdrawal, alterations in membrane properties, including increased input re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
68
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 35 publications
11
68
0
Order By: Relevance
“…Our findings are consistent with previous electrophysiological studies reporting inhibition of mPFC activity by amphetamine under anesthesia (Mora et al, 1976) and alteration in membrane excitability and evoked firing rate in vitro (Peterson et al, 2000;Dong et al, 2005;Nasif et al, 2005). Our observation of the rapid onset of plasticity at the level of PFC neuronal ensembles suggests that other measures of psychostimulant-induced plasticity with delayed onset (Wolf, 1998;Porrino and Lyons, 2000;Nestler, 2004;Robinson and Kolb, 2004) may be secondary to changes in cortical firing.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with previous electrophysiological studies reporting inhibition of mPFC activity by amphetamine under anesthesia (Mora et al, 1976) and alteration in membrane excitability and evoked firing rate in vitro (Peterson et al, 2000;Dong et al, 2005;Nasif et al, 2005). Our observation of the rapid onset of plasticity at the level of PFC neuronal ensembles suggests that other measures of psychostimulant-induced plasticity with delayed onset (Wolf, 1998;Porrino and Lyons, 2000;Nestler, 2004;Robinson and Kolb, 2004) may be secondary to changes in cortical firing.…”
Section: Discussionsupporting
confidence: 92%
“…Blockade of these outflowing K ϩ currents leads to depolarization from RMP (Nasif et al 2005). Because these K ϩ channels belong to the superfamily of the inward rectifier and activity of inwardly rectifying K ϩ channels is reduced with D 2 R stimulation (see above), we also studied whether the RMP of NAc neurons was modulated by D 2 Rs.…”
Section: R Stimulation Depolarized Rmpmentioning
confidence: 99%
“…These K ϩ channels are highly expressed in the NAc (Karschin et al 1996;Talley et al 2001). Blockade of this K ϩ efflux depolarizes RMP in neurons (Nasif et al 2005). Our findings not only show a D 2 R-modulated membrane depolarization from RMP, but also unmask its mechanism in which activation of PI-PLC was responsible for this D 2 R action on decreasing "leak" K ϩ currents.…”
Section: R-mediated Depolarization Of Rmp Is Also Modulated By Acmentioning
confidence: 99%
See 1 more Smart Citation
“…Arguing against this possibility, recent studies in dissociated PFC pyramidal cells after withdrawal from cocaine demonstrate increased excitability as a result of a decreased voltage-gated and inwardly rectifying I k and enhanced L-type I Ca2ϩ (Dong et al, 2005;Nasif et al, 2005a). Moreover, Nasif et al (2005b) showed that repeated cocaine administration increased the membrane excitability of PFC neurons in slices. The apparent contradictory findings on excitability between recordings in vitro and in vivo suggest that cocaine-induced neuroadaptations in the circuit in which the PFC pyramidal cells are embedded are critically affecting excitability.…”
Section: Repeated Treatment With Cocaine Depresses Evoked Cortical Exmentioning
confidence: 99%